The universal methods of building the image of a little man in the works of N.V. Gogol (On the narrative strategy and reception) - E.V. Sintsov (Ученые записки Казанского университета: Серия Гуманитарные науки)
This paper aims at identification of the universal narrative techniques and principles developed by N.V. Gogol to express his views about a little man. On the basis of the narrative strategy, the conceptual core of understanding of a little man by N.V. Gogol has been created. Special techniques and semantic levels of the dialogue with the reader created by the author of the works, in which the above-specified type of character occurs, have been “modeled”. The research is based on such N.V. Gogol's works as “The Government Inspector” and “Dead Souls”, as well as some individual images from such series as “St. Petersburg Stories”, “Evenings on a Farm Near Dikanka”, and “Mirgorod”. This triune approach (the author's concept – the narrative strategy – the principles of dialogue with the reader) has allowed to reveal new philosophical and artistic aspects of the image of a little man, to establish their connection with the sharp contrast of “the hidden” and “the visible” in the unfolding of the narrative structures, and to describe the conditions for a sudden displacement of contemplative and ironic position of the reader in terms of intuitive reading of riddles of the soul of the characters. The first part of the paper summarizes the observations of literary scholars over the techniques that shape the effect of hiddenness: the details indirectly characterizing the characters, their relationships with others, portrait features, description of the actions, dreams. It has been concluded that the techniques are focused on the generation of an illusion in the reader that the character is understood from different sides, being built following the principle of mosaicity. The author creates a feeling of a certain “preparation” of the character in the reader, which is similar to a distant observation, leading to the final and comprehensive conclusions. This position invariably gives way to the intuitive and empathic “empathy” of the true essence of the character. This occurs in special episodes, in which the character has an intense fear (Chertokutskii, who found shelter in a carriage; Khoma under the look of the Viy; an important man in front of Bashmachkin's ghost), inspired by love (monologues held by Poprishchin, Podkolesin, Vakula, and Andriy), or experiences a rare feeling of harmony with the world and themselves (the panorama of Rome in front of the young Prince; the silence of Chichikov who escaped from the city). In these episodes, N.V. Gogol expressed his idea of mysteries of the human soul inconceivable by the mind: its sacrifice, childness, ability to love with whole heart, etc. Thus, the writer inspires the reader with the idea of sacredness of the soul, its being hidden in everyday spaces, relations between a little man and the eternal values of humanity and mystical dimensions. The materials of the paper can be used both in school and academic teaching of the Russian literature of the 19th century (the works of N.V. Gogol).